Evaluation of Front Line Demonstration on Drought Tolerant Rice (Oryza sativa L.) Variety Satyabhama in Mid Central Table Land Zone of Odisha - Samant, Tiryak Kumar (International Journal of Bio-resource and Stress Management, 2017)
he study was carried out through front line demonstrations during kharif season of 2015 and 2016 in mid central table land zone of Odisha with an objective to evaluate the performances of improved practice of drought tolerant high yielding variety (HYV) rice Satyabhama as compared to the local check (Khandagiri). Satyabhama matured at 110 days, recorded higher plant height (103.76 cm), effective tillers plant-1 (12.44), length of panicle (23.2 cm), filled grains panicle-1 (129.72), spikelet fertility (92.29%) and 1000 grain weight (23.4 g) than Khandagiri. The same also produced grain yield 40.83 q ha-1 which is 40.94% higher than Khandagiri with harvest index (46.72%) and production efficiency (37.12 kg ha-1 day-1). The HYV rice Satyabhama gave higher gross return Rs. 63493.9 ha-1 with a benefit-cost ratio 1.98, profitability (Rs. 85.92 ha-1 day-1) and additional net return Rs. 13424.15 ha-1 as compared to farmers practice and the study showed that horizontal spread of area from 1.0 ha during 2015 to 25 ha during 2016 under improved technology with technological gap, extension gap and technology index; 19.17 q ha-1, 11.86 q ha-1, 31.95% respectively. The growth and yield performance of Satyabhama was found to be satisfactory in spite of occurrence of frequent dry spells during different crop growth stages. Thus the existing variety Khandagiri may be replaced by Satyabhama for higher productivity, income and drought tolerant capacity.